Policy and Programs for Cycling in the City of Zagreb – A Critical Review - Pilko, Hrvoje; Tepeš, Krunoslav; Brezina, Tadej (Promet - Traffic&Transportation, 2015)
Studying cycling traffic issues in a beginner city – City of Zagreb, stems from unclear development policy, an increase in cycling volume, a large number of traffic accidents, an inadequate infrastructure and legislation, a small number of high quality studies and published papers, and the question, did current cycling policy and programs advance cycling? A comprehensive search of available literature, including data from the Zagreb Traffic Department, was made. These data do not adequately address the direction of causality, such as whether current cycling policy and programs advance cycling or whether cycling demand led to increased levels of cycling. This review paper suggests that, it is not yet possible to evaluate which pro-bicycle packages are the most effective and, development of cycling traffic requires a coordinated holistic planning strategy. Results could serve as a beacon light for similarly sized beginner cities, especially those who are located in South-eastern and Eastern Europe.